Pulse shaping approach to PAPR reduction for OFDM communication systems - Hendranata, Regina Reine (Curtin University, 2015)
One of the main drawbacks of the OFDM communication system is the high peak-to-average-power ratio (PAPR) of the transmitted signal. In this thesis: (i ) Optimal pulse shaping filter design is proposed to reduce the PAPR of the OFDM signal; (ii ) The level crossing rate theorem is used to derive an upper bound for the CCDF of PAPR of OFDM signal with pulse shaping; (iii ) The multiple filter design is proposed to reduce the PAPR of multiuser OFDM signal.